Programmed cell death in tumor immunity: mechanistic insights and clinical implications - Wang, Man; Yu, Fei; Zhang, Yuan; Li, Peifeng (Frontiers in Immunology, 2024)
Programmed cell death (PCD) is an evolutionarily conserved mechanism of cell suicide that is controlled by various signaling pathways. PCD plays an important role in a multitude of biological processes, such as cell turnover, development, tissue homeostasis and immunity. Some forms of PCD, including apoptosis, autophagy-dependent cell death, pyroptosis, ferroptosis and necroptosis, contribute to carcinogenesis and cancer development, and thus have attracted increasing attention in the field of oncology. Recently, increasing research-based evidence has demonstrated that PCD acts as a critical modulator of tumor immunity. PCD can affect the function of innate and adaptive immune cells, which leads to distinct immunological consequences, such as the priming of tumor-specific T cells, immunosuppression and immune evasion. Targeting PCD alone or in combination with conventional immunotherapy may provide new options to enhance the clinical efficacy of anticancer therapeutics. In this review, we introduce the characteristics and mechanisms of ubiquitous PCD pathways (e.g., apoptosis, autophagy-dependent cell death, pyroptosis and ferroptosis) and explore the complex interaction between these cell death mechanisms and tumor immunity based on currently available evidence. We also discuss the therapeutic potential of PCD-based approaches by outlining clinical trials targeting PCD in cancer treatment. Elucidating the immune-related effects of PCD on cancer pathogenesis will likely contribute to an improved understanding of oncoimmunology and allow PCD to be exploited for cancer treatment.